Effect of ACE-inhibition on coronary microvascular function and symptoms in normotensive women with microvascular angina: A randomized placebo-controlled trial. - Marie Mide Michelsen; Anna Bay Rask; Elena Suhrs; Kristoffer Flintholm Raft; Nis Høst; Eva Prescott (PLoS ONE)
Objective Studies have suggested a beneficial effect of angiotensin-converting enzyme (ACE) inhibition. To explore whether the ACE inhibitor ramipril has a direct effect on the microvasculature beyond the blood pressure (BP) lowering effect, we investigated whether ramipril improved coronary microvascular function in normotensive women with coronary microvascular dysfunction (CMD). Methods We included 63 normotensive women with angina, no epicardial stenosis>50% and CMD defined as a coronary flow velocity reserve (CFVR)<2.2 assessed by adenosine stress-echocardiography in a randomized double-blinded, superiority trial with 1:1 allocation to placebo or ramipril (maximum dose 10 mg depending on blood pressure) for 24±6 weeks. Primary outcome was CFVR. Secondary outcomes were left ventricular systolic and diastolic function and symptoms evaluated by Seattle Angina Questionnaire (clinicaltrials.gov, NCT02525081). Results Follow-up was available on 55 patients. BP remained unchanged during treatment in both groups. CFVR improved in both the ramipril (p = 0.004) and placebo group (p = 0.026) with no difference between groups (p = 0.63). Symptoms improved in both groups with no significant between-group differences. No changes were detected in parameters of systolic and diastolic function. No serious adverse reactions were reported. Conclusions In normotensive women with angina and CMD, treatment with ramipril had no significant effect on CFVR or symptoms compared with placebo. The effect of ACE inhibition previously reported may be mediated by blood pressure reduction.